H-2, D-2 and HD adsorption upon the metal-organic framework [Cu2.97Zn0.03(btc)(2)](n) studied by pulsed ENDOR and HYSCORE spectroscopy - Jee, Bettina; Hartmann, Martin; Poeppl, Andreas (Molecular Physics, 2013)
The adsorption of hydrogen has become interesting in terms of gas separation as well as safe and reversible storage of hydrogen as an energy carrier. In this regard, metal-organic framework compounds are potential candidates. The metal-organic framework [Cu2.97Zn0.03(btc)(2)](n) as a partially Zn-substituted analogue of the well known compound HKUST-1 is well suited for studying adsorption geometries at cupric ions by electron paramagnetic resonance (EPR) methods due to the formation of few mixed Cu/Zn paddle wheel units with isolated S = 1/2 electron spins. The adsorption of hydrogen (H-2) as well as the deuterium (D-2) and HD molecules were investigated by continuous wave EPR and pulsed ENDOR and HYSCORE spectroscopy. The principal values of the proton and deuterium hyperfine coupling tensors A(H) and A(D) were determined by spectral simulations as well as of the deuterium nuclear quadrupole tensor Q(D) for adsorbed HD and D-2. The results show a side-on coordination of HD and D-2 with identical Cu-H and Cu-D distances r(CuX) = 2.8 angstrom with the tensors A(H,D) and Q(D) aligned parallel to the C-4 symmetry axis of the paddle wheel unit. A thermodynamic non-equilibrium state with J = 1, m(J) = +/- 1 is indicated by the experimental data with A(H,D) and Q(D) averaged by rotation around C-4.
Keywords: orientation-selective pulsed EPR spectroscopy; hydrogen adsorption; HKUST-1; deuterium nuclear quadrupole splitting